Study on flow and heat transfer characteristics of liquid metal flow in narrow rectangular channels under high heat flux - Zhang, Xue; Feng, Wenpei; Yu, Hongxing; Deng, Jian; Du, Sijia; Wang, Xiaoyu (Frontiers in Energy Research, 2024)
In order to improve the core power density of liquid metal reactors, narrow rectangular fuel assemblies are typically used, which have obvious advantages in heat transfer capacity. However, the flow and heat transfer characteristics in coolant passage need to be studied. In this article, the numerical simulation analysis model obtained earlier was applied to calculate the Nusselt number, friction factor, with different Reynolds number, Prandtl number, or Peclet number of lead bismuth flow in a narrow rectangular channel under high heat flux. A heating correction factor was proposed and a flow resistance model was established for high heat flux. The influencing factors of ultra-high flux reactor core, such as gap size, flow direction, single and double sided heating conditions, on the flow and heat transfer in narrow rectangular channels were explored. The results showed that gap size and aspect ratio have a certain impact on the Nu and f of narrow rectangular channels, but the influence is relatively small within the narrow rectangular channel condition range. The influence of flow direction on flow and heat transfer is minimal, the single and double sided heating conditions will bring about a difference of about 20% in Nu and a difference of about 2.5% in f. In addition, the type of liquid metal will also affect the results. The research can provide reference for the thermal design and optimization of ultra-high flux reactor cores.